Alat Pembakar Sampah Berbahan Oli Bekas Untuk Mengurangi Emisi Gas Buang Dan Residu Pembakaran - Fita Lestari, Riska; Ratna Mustika Yasi; Adi Mulyadi; Lutfi Irawan Rahmat; Muhamad Khoirul Anam; Ma’ruf Amin (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
The problem of waste and used oil waste is a serious challenge in environmental management. Waste that is not managed properly can pollute the environment, while used oil that is disposed of carelessly has the potential to pollute soil and water. This research aims to design and test a used oil-fueled garbage burner as a solution in reducing environmental impacts. The research method used is the experimental method, which includes designing, manufacturing, and testing the burner. Tests were conducted to measure combustion efficiency, fuel consumption, and exhaust emissions. Data were collected through direct observation and quantitative analysis using a gas analyzer to measure the levels of CO, CO₂, SO₂, NOx, and particulates produced. The results show that this device is able to burn waste more efficiently than conventional methods. The use of used oil as an alternative fuel also helps reduce oil waste that is harmful to the environment. However, although the burner significantly reduced the volume of waste, the exhaust gas analysis showed that improvements in the emission filtering system are still needed to minimize the impact of air pollution. In conclusion, the used oil-fueled waste burner can be an innovative solution in waste and waste oil management, but it needs further development to improve its environmentally friendly aspects. The recommendation of this research is the implementation of an exhaust gas filtration system as well as further testing to adapt the appliance to applicable environmental standards.